Study of structural, dielectric, optical properties and electronic structure of Cr-doped LaInO3 perovskite nanoparticles - Kumar S.; Dwivedi G.D.; Joshi A.G.; Chatterjee S.; Ghosh A.K. (My University, 2025)
This work reports the change in the structural, dielectric and optical behaviour of Cr-doped LaInO3 nanoparticles synthesized via sol-gel method. X-ray diffraction patterns confirm that systems crystallize in orthorhombic Pnma space group. Raman spectroscopy measurements exhibit blue-shift in Raman modes with Cr-doping due to the compressive stress introduced by smaller Cr3 + cations. Trivalent oxidation state of Cr was confirmed from Cr(2p) core-level X-ray photoemission spectroscopy measurements, while valence band spectra suggest the absence of electronic states near Fermi level. High-resolution Ultraviolet photoemission spectra near Fermi level shows the electronic density of states arises sharply near Fermi level. Room temperature dielectric constant decreases with increasing Cr-concentration, which shows that conductivity has been increased after Cr-doping. Ultraviolet–visible spectroscopy measurements provide band gap of 4.8 eV for LaInO3 and Cr-doped LaInO3nanoparticles.Moreover, Cr-doped LaInO3systems exhibit an intermediate band gap of 3 eV, which might have been created from Cr(3d) states. © 2017 Elsevier Inc.